Topical Prostaglandin E Analog Restores Defective Dendritic Cell-Mediated Th17 Host Defense Against Methicillin-Resistant Staphylococcus Aureus in the Skin of Diabetic Mice - Dejani, Naiara N. [UNESP]; Brandt, Stephanie L.; Pineros, Annie; Glosson-Byers, Nicole L.; Wang, Sue; Son, Young Min; Medeiros, Alexandra I. [UNESP]; Serezani, C. Henrique (Amer Diabetes Assoc, 2016)
People with diabetes are more prone to Staphylococcus aureus skin infection than healthy individuals. Control of S. aureus infection depends on dendritic cell (DC)-induced T-helper 17 (Th17)-mediated neutrophil recruitment and bacterial clearance. DC ingestion of infected apoptotic cells (IACs) drive prostaglandin E-2 (PGE(2)) secretion to generate Th17 cells. We speculated that hyperglycemia inhibits skin DC migration to the lymph nodes and impairs the Th17 differentiation that accounts for poor skin host defense in diabetic mice. Diabetic mice showed increased skin lesion size and bacterial load and decreased PGE2 secretion and Th17 cells compared with nondiabetic mice after methicillin-resistant S. aureus (MRSA) infection. Bone marrow-derived DCs (BMDCs) cultured in high glucose (25 mmol/L) exhibited decreased Ptges mRNA expression, PGE2 production, lower CCR7-dependent DC migration, and diminished maturation after recognition of MRSA-IACs than BMDCs cultured in low glucose (5 mmol/L). Similar events were observed in DCs from diabetic mice infected with MRSA. Topical treatment of diabetic mice with the PGE analog misoprostol improved host defense against MRSA skin infection by restoring DC migration to draining lymph nodes, Th17 differentiation, and increased antimicrobial peptide expression. These findings identify a novel mechanism involved in poor skin host defense in diabetes and propose a targeted strategy to restore skin host defense in diabetes.